The US dollar and trade balance: New findings from the international trade of India with the European Union - Ho Hoang Gia Bao; Hoang Phong Le; Ba Hoang Nguyen; Thanh An Vu (Cogent Business & Management, 2023)
The US dollar is the most prevalent currency to settle internationally traded merchandise. A few existing studies demonstrate that the US dollar can significantly impact a country's trade balance with a non-US partner. Nevertheless, the current literature indicates the remarkable deficiency of empirical results for the case of India despite the vital importance of the US dollar in its international trade. Recognizing the European Union (EU) as the largest trading partner of India over the 2000Q1-2022Q2 period, this study is the first to explore how the US dollar influences India's trade balance with the EU by employing the Nonlinear Autoregressive Distributed Lag (NARDL) method. The results show that, no matter if the US dollar is employed, the depreciation of rupee cannot facilitate India's trade balance, and the appreciation has a negative effect. Therefore, devaluation is an ineffectual policy for supporting India's trade balance with the EU.
Keywords: F10; F31; F40; 650; EU; India; nonlinear; rupee; trade balance; US dollar